A study of arts and crafts, Ban Mon Nakhon Sawan pottery for the development of local wisdom - Kaewduk, Kittisak; Dinfa, Patcharee (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2023)
This academic article is an article that creates and develops a product model to promote the group of pottery entrepreneurs of Ban Mon community, Ban Kaeng Sub-district, Mueang Nakhon Sawan District. The article is a guideline for developing the model and promoting local wisdom to create a new style of plant pot. The original pattern can be divided into seven types of pot patterns including 1) Orchid-shaped pot design 2) Candy-shaped pot design 3) Brick-shaped pot design 4) Round-rimmed pot 5) Bullet-shaped pot 6) Azalea-shaped pot 7) Little pot. Ban Mon Pottery should develop in pursuance of enhanced knowledge and developed wisdom for local producers by adopting the existing model brought to create and develop local values to increase the product value with tangible results. The purpose of this article is to add value in terms of usefulness and beauty to meet standards and be disposed to build a foundation economy to build the strength of the community in the next step.